Transcriptional Regulation of Urokinase-type Plasminogen Activator Receptor by Cyclic AMP in PL-21 Human Myeloid Leukemia Cells: Comparison with the Regulation by Phorbol Myristate Acetate - Niiya, Kenji; Ozawa, Tetsuo; Tsuzawa, Toyokazu; Ueshima, Shigeru; Matsuo, Osamu; Sakuragawa, Nobuo (Thrombosis and Haemostasis, 1998)
We investigated the effect of dibutyryl cyclic AMP (Bt2-cAMP) on urokinase-type plasminogen activator receptor (uPAR) expression in human PL-21 myeloid leukemia cells and compared it with the effect of phorbol myristate acetate (PMA). Flow cytometric analysis clearly demonstrated that Bt2-cAMP and PMA both induced the cell surface expression of uPAR. Northern analysis and nuclear run-on assay revealed that cAMP and PMA activated the uPAR gene transcription and both additively increased the uPAR mRNA level. However, actinomycin-D decay experiment showed that PMA, but not cAMP, prolonged the uPAR mRNA half-life. Furthermore, inhibition of the ongoing protein synthesis with cycloheximide abrogated completely the PMA-induced uPAR mRNA accumulation but only partially the induction by PMA plus cAMP, whereas the induction by cAMP alone was rather amplified, indicating that the de novo protein synthesis is necessary in the induction by PMA but not in the induction by cAMP and that the cAMP pathway may be dominant in uPAR gene expression in the PL-21 cells as compared to the PMA pathway. These results suggest that cAMP induces the uPAR expression exclusively through activating the gene transcription in which a preexisting transcriptional factor may be involved, whereas PMA transcriptionally and post-transcriptionally regulates the uPAR gene expression.